2022
DOI: 10.3390/ijms23105560
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cognitive Function in Ovariectomized Rats by Human Neural Stem Cells Overexpressing Choline Acetyltransferase via Secretion of NGF and BDNF

Abstract: Menopause is associated with memory deficits attributed to reduced serum estrogen levels. We evaluated whether an increase in brain-derived neurotrophic factor (BDNF) and nerve-growth factor (NGF) levels, through transplantation of choline acetyltransferase (ChAT)-overexpressing neural stem cells (F3.ChAT), improved learning and memory in ovariectomized rats. PD13 mouse neuronal primary culture cells were treated with estradiol or co-cultured with F3.ChAT cells; choline transporter1 (CHT1), ChAT, and vesicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…However, treatment with post-fermented GBE counteracted the effect of AF64A, enhancing the activity of the cholinergic nervous system. This increase in activity was attributed to increased expression of NGF and BDNF, which prevent nerve cell death and promote their proliferation, as well as increased activity of the cholinergic nervous system [12,[53][54][55]. Thus, an increase in ginsenosides, such as Rg3, Rg5, and Rk1, in postfermented GBE seems to inhibit inflammation caused by AF64A and increase antioxidant effects to protect cells [56,57], as well as increase BDNF and NGF to regulate the expression of the cholinergic nervous system [58][59][60].…”
Section: Discussionmentioning
confidence: 98%
“…However, treatment with post-fermented GBE counteracted the effect of AF64A, enhancing the activity of the cholinergic nervous system. This increase in activity was attributed to increased expression of NGF and BDNF, which prevent nerve cell death and promote their proliferation, as well as increased activity of the cholinergic nervous system [12,[53][54][55]. Thus, an increase in ginsenosides, such as Rg3, Rg5, and Rk1, in postfermented GBE seems to inhibit inflammation caused by AF64A and increase antioxidant effects to protect cells [56,57], as well as increase BDNF and NGF to regulate the expression of the cholinergic nervous system [58][59][60].…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study has demonstrated the association between estrogen deficiency and cognitive dysfunction, particularly memory loss. (Yoon et al, 2021(Yoon et al, , 2022. Angiogenesis-related factors have been proposed as potential candidates for restoring vascular function and alleviating these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of exosomes were measured by size, particle number, and exosome markers [ 24 ]. Especially, in the coculture with TSG101 cells, since exosomes are smaller than 0.4 μm, only exosomes were secreted at the 0.4 μm membrane, and at the 4.0 μm membrane, cells and exosomes affected N2A cells together [ 25 , 26 ]. These results were consistent with those obtained in N2A cells subjected to OGD and in the brain after MCAO.…”
Section: Discussionmentioning
confidence: 99%